Elementary School Students' Mental Health during the Corona Virus Pandemic (COVID-19) - Elisabeth Desiana Mayasari; Laurensia Aptik Evanjeli; Brigitta Erlita Tri Anggadewi; Puji Purnomo (Journal of Psychology and Instruction, 2021)
During the Coronavirus (COVID-19) pandemic, changes in routine have affected students’ psychological development. This study aims to determine elementary school students’ mental health during the Corona Pandemic. The benefit of this research is as a basis for efforts to prevent and overcome unexpected psychological conditions in students. This research is a descriptive quantitative study using a survey method. The population in this study were 148 students aged 9-14 years. The data collection technique used was a questionnaire. This study used the Indonesian version of Strength and Difficulty Questionnaire for Children (SDQC) arranged by Robert Goodman. The result showed that the condition of the students was in the "abnormal" category which was indicated by a condition that was less good than the condition in general. There were 17 (11.49%) students in the abnormal category on the disruptive behaviour subscale, 11 (7.43%) students on the hyperactive-inattention subscale, 10 (7%) students on the emotional subscale, 5  (3%) students on the indifference subscale, and 2 (1%) students on the relation problems subscale. Overall aspects of measurement show that the students show a state of "abnormal" status in one or two aspects and it means that students have good mental health.